Bouveret Syndrome: A Rare Case of Instance and Treatment in a Younger Patient - Kevin J. Yang; C. K. Chang (Case Reports in Gastrointestinal Medicine)
Bouveret syndrome, a specific form of gallstone ileus, is the obstruction of the gastric outlet by a gallstone, which can enter the duodenum through a fistula. While the average age of individuals with Bouveret syndrome is 74 years, our patient was 42 years of age at the time of operation, significantly younger than the average patient afflicted with this condition. In the treatment of our patient’s condition, the operation conducted entailed a partial duodenectomy, gastrojejunostomy, cholecystectomy, common bile duct exploration, extraction of bile duct stones, and insertion of a t-tube in the bile duct. The patient was found to be in healthy condition upon check-up six months after the operation. The outcome of our case suggests that younger Bouveret patients can safely undergo multiple surgical procedures in the treatment of Bouveret syndrome. Our case also suggests that a cholecystectomy and the removal of the obstructing gallstone can both be carried out within one operation, although coupling these two procedures in one operation might be riskier for patients within the normal age range of Bouveret syndrome. We also suggest that fistula repair be carried out for younger Bouveret patients in particular and that the patient be subjected to a CT scan in the diagnosis of Bouveret syndrome when this condition is suspected.